Definição do regime jurídico de licitação e contratos das empresas estatais: análise dos critérios dicotômico, concorrencial e modelo empresarial - Débora Carvalho Mascarenhas dos Anjos (2019)
This dissertation seeks to analyze, in light of the 1988 Republic’s Constitution, whether the dichotomous criterion is determinant for the definition of the legal regime of bidding and contracts of the state-owned companies and if Law number 13.303/2016, in the part that is relative to the topic, applies to all state-owned companies, regardless of the activity performed. The research’s hypothesis consisted on the affirmation that the competitive criterion is determinant for the definition of the legal regime of bidding and contracts of the state-owned companies. As a theoretical framework, the work utilizes the classification proposed by Eros Roberto Grau, according to whom economic activities are those that are destined to satisfy the necessities of collectivity by means of the utilization of goods and services. Thus, both the public services and the economic activities in a strict sense are species of the gender economic activity in a broad sense. In order to achieve the general objective proposed, the methodology belonging to the legal-dogmatic angle was adopted. Stemming from the analysis of norms, doctrinal texts, legislation, as well as from the investigation of certain judgements, it was concluded that neither the dichotomous criterion nor the competitive one are determinant for the definition of the legal regime of bidding and contracts of the state-owned companies, but rather the criterion of the business model. It was also concluded that the Law number 13.303/2016 does not apply to all state-owned companies, regardless of the activity performed by them.